Perkembangan Ilmu Psikologi Belajar dalam Mendukung Praktik Bimbingan Konseling di Abad 21; Behavioristik ke Konstruktivisme - Sandra, Rober; N, Neviyarni; Nirwana, Herman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The paradigm shift in learning psychology from behaviorism to constructivism is crucial in addressing the increasingly complex and dynamic challenges of 21st-century education and guidance counseling. This article aims to explore the evolution of learning psychology theories and their implications for modern counseling practices. Using a qualitative approach through literature study, this research reviews academic. Data collection was conducted through document analysis, and the data were interpreted using content analysis techniques. The findings reveal that constructivist approaches are more adaptive in fostering self-awareness and personal meaning-making in clients compared to behaviorist models. This study reinforces the relevance of constructivist theory in contemporary counseling practices and highlights the need to integrate learning psychology into counseling services grounded in humanistic values. The conclusion emphasizes the importance of reflective counseling strategies and suggests further empirical studies for practical implementation.